Exploring the codon patterns between CCD and NCED genes among different plant species. (November 2019) - Priya, R.; Sneha, P.; Dass, J. Febin Prabhu; Doss C, George Priya; Manickavasagam, M.; Siva, Ramamoorthy
Abstract: Plant carotenoid cleavage oxygenase ( CCO ) is an enzyme which catalyzes carotenoids to apocarotenoid products that are involved in several vital physiological functions. The CCO exists in two forms, namely, CCD (Carotenoid Cleavage Dioxygenase) and NCED (Nine-Cis Epoxycarotenoid Dioxygenase). This paper relates to a comparative study on CCD and NCED genes through phylogeny and codon usage analysis. The result of the phylogenetic analysis indicates a closer relationship between CCD and NCED subclass genes, while the RSCU values indicate a high preference for CUC codon in both CCD and NCED gene families. The mean ENc value of NCED genes was found to be 48.76, suggesting a higher codon bias compared to CCD genes. However, the ENc-GC3S plot suggests that both the gene families are under mutational pressure with variations according to their species-specific role. Similarly, the multivariate analysis also suggests that nucleotide mutation bias influences codon usage. Correlation analysis of Axis I and codon adaptation index values indicate a significant correlation between critical indices. Even though the prominence of the variations in codon usage between the two gene families, they are exerted towards the time-specific functional requirement for that plant species. This is evident from the cleaving roles of these enzymes against various carotenoids at different growth stages. The result of this investigation indicates that CCD and NCED genes are under mutational pressure. This codon bias study paves the way for increasing the production of apocarotenoids, which have a great significance in the industry. Highlights: Comparative study on CCD and NCED genes through phylogeny and codon usage. Closer relationship of CCD and NCED subclass genes. Both CCD and NCED genes are under mutational pressure.